SOCIAL CRITICISM IN KONSPIRASI ALAM SEMESTA NOVEL BY FIERSA BESARI - Hapni Nurliana H.D Hasibuan; Anwar Effendi; Margana Margana (Universitas Padjadjaran, 2021)
Every litterateur makes existing issues or phenomena as inspiration in making literary works. In case with novelist, they convey criticism expressly or implicitly in their novel. Besides the love story, the Konspirasi Alam Semesta novel by Fiersa Besari, the author also criticizes the social conditions that exist in Indonesia. Social criticism in the novel will be the purpose of this research. Furthermore, this research focuses on analyzing the Konspirasi Alam Semesta novel using a sociological literary approach with social criticism. The research method is qualitative research methods with reading and note-taking techniques. The purpose of the research is to describe the problem of social criticism and the form of its presentation in the novel. The research result has obtained: (1) social criticism about politics such as discrimination against families of ex- political prisoner, government policies towards those who have made the country proud, Papua’s wealth and injustice in the development of remote areas, (2) moral criticism of corruption, (3) social criticism of humanity such as generalizations about a group, individual differences, violence against separatists and stigma about spinster, (4) social criticism about religion / belief about the creator. It can be concluded that the author implicitly conveyed his message and response through the Konspirasi Alam Semesta novel. It describes conditions that deviate from social conditions that must be criticized. This novel revives the people’s insights about social problems that exist in Indonesia. Furthermore, the author’s main topic of social criticism is political and humanitarian in Indonesia.